2020
DOI: 10.2147/cmar.s274992
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Pelvic Lymphadenectomy on Survival in Patients with Low-Risk Early-Stage Endometrial Cancer Diagnosed Intraoperatively Using Frozen Tissue Sections: A Retrospective Analysis</p>

Abstract: Purpose To determine whether pelvic lymphadenectomy improved survival in patients diagnosed with low-risk early-stage endometrial cancer by intraoperative pathology. Methods This retrospective analysis included 238 patients at our hospital. Results The lymphadenectomy and non-lymphadenectomy groups contained 121 and 117 patients, respectively. In both groups, more than half the patients had tumor size ≥2 cm, and most had myometrial invasion <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This is in line with our and the previously presented data, which indicate that the systematic lymphadenectomy does not improve overall survival rates. Further studies have also shown that lymph node dissection does neither improve overall survival nor progression-free survival in patients with endometrial cancer [13,32,33]. Benedetti et al observed an overall survival rate of 85.9% in patients who underwent a lymphadenectomy versus 81.7% in patients without lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our and the previously presented data, which indicate that the systematic lymphadenectomy does not improve overall survival rates. Further studies have also shown that lymph node dissection does neither improve overall survival nor progression-free survival in patients with endometrial cancer [13,32,33]. Benedetti et al observed an overall survival rate of 85.9% in patients who underwent a lymphadenectomy versus 81.7% in patients without lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our data, which indicated that systematic lymphadenectomy does not improve overall survival rates. Further studies have also shown that lymph node dissection does neither improve overall survival nor progression-free survival in patients with endometrial cancer [13,31,32]. Benedetti et al observed an overall survival rate of 85.9 % in patients who underwent a lymphadenectomy versus 81.7 % in patients without lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%